Assembly and architecture of the Wnt/β‐catenin signalosome at the membrane - DeBruine, Zachary J (Br J Pharmacol, 2017)
Wnt/β‐catenin signalling is initiated by a ternary Wnt‐Frizzled (FZD)‐LDL receptor‐related protein (LRP) 5/6 binding event. The resulting conformational changes in the FZD and LRP5/6 receptors promote the assembly of an intracellular signalosome driven by Dishevelled and Axin co‐polymerization. Recent evidence suggests that the FZD receptor and LRP5/6 participate in the assembly of this signalosome by forming regulatory scaffolds for stabilizing Dishevelled and Axin adapters. In this review, we focus on the contributions of Wnts and their receptors in the assembly of the signalosome. We present an emerging model, which unifies Wnt receptor oligomerization with intracellular signalosome formation, and then discuss how FZD receptors might be targeted to either disrupt or enhance their capacity as a dynamic sensor of Wnt binding. LINKED ARTICLES: This article is part of a themed section on WNT Signalling: Mechanisms and Therapeutic Opportunities. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v174.24/issuetoc